The Warburgian Narrative on the "Survival of the Classics" as a Jewish Construct in a Christian World - Weber, Regina (ARJ – Art Research Journal: Revista de Pesquisa em Artes, 2022)
The exclusion of German-Jewish scholars from the German scientific community already at the time of the Weimar Republic before the National Socialist persecution caused the art historian Aby Warburg and his circle to look for a new and positive positioning in German intellectual life. In my paper I want to show that Aby Warburg's Kulturwissenschaftliche Bibliothek with its interdisciplinary program of collection and research on the "survival of the classics", including the fields of art and culture, history of philosophy and religion, is constructed as a very original competing narrative in contrast to the predominant Christian "Heilsgeschichte". Whereas Aby Warburg himself showed the 'survival of the classics' in the masterpieces of the Italian Renaissance, the philosopher Ernst Cassirer and the historian of philosophy Raymond Klibansky made apparent the continuity of the Platonic tradition from Late Antiquity to the Middle Ages and the Renaissance.